2012
DOI: 10.1620/tjem.226.267
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Checkpoint Kinase 1 Is Associated with the Increased Radiosensitivity of Glioblastoma Stem-Like Cells

Abstract: Glioblastoma multiforme is an aggressive brain tumor with a poor prognosis. The glioblastoma stem-like cells (GSCs) represent a rare fraction of human glioblastoma cells with the capacity for multi-lineage differentiation, self-renewal and exact recapitulation of the original tumor. Interestingly, GSCs are more radioresistant compared with other tumor cells. In addition, the remarkable radioresistance of GSCs has been known to promote radiotherapy failure and therefore is associated with a significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Knockdown of Chk1 and Chk2 kinases with siRNA has proven effective in vitro in preventing cell cycle arrest and inducing apoptosis [99]. Checkpoint, ATM and other inhibitors are of avid interest in decreasing cell cycle arrest, promoting apoptosis after DNA damage from alkylating chemotherapy or radiation [100103].…”
Section: Targeted Therapies Toward Glioma Stem Cells (That May Be mentioning
confidence: 99%
“…Knockdown of Chk1 and Chk2 kinases with siRNA has proven effective in vitro in preventing cell cycle arrest and inducing apoptosis [99]. Checkpoint, ATM and other inhibitors are of avid interest in decreasing cell cycle arrest, promoting apoptosis after DNA damage from alkylating chemotherapy or radiation [100103].…”
Section: Targeted Therapies Toward Glioma Stem Cells (That May Be mentioning
confidence: 99%
“…Bao et al (2006) have found that the proportion of survived CD133-positive GSLCs after radiation was increased relative to that of CD133-negative GDCs, and this finding was attributed to greater activation of checkpoints, such as ATM, Rad17, Chk1, and Chk2, in response to irradiation. Additionally, recent studies have shown that Chk1, but not Chk2, exerts dominant functions in the DNA damage repair of GSLCs after irradiation (Uto et al 2004;Wu et al 2012;Bo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al (2014b) found that the removal of Brachyury that was related to cell proliferation, migration, invasion, radiation and chemotherapy resistance of Adenoid Cystic carcinoma CSCs could improve tumor stem cell radiation sensitivity. Wu et al (2012a) developed a model of CDK1 knock-out brain malignant glioma and found that CDK1 contributed to enhance radiosensitivity of CSCs by inducing cell apoptosis. Cell cycle checkpoint kinases (CDK1 and CDK2) play key roles in DNA damage response in radiation and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%